Нelicobacter pylori as etiological factor of acute pancreatitis and marker of its purulent-septic complications development - І. V. Коlosovych; І. V. Hanol; К. О. Lebedieva (Клінічна хірургія)
Objective. Studying of role of Нelicobacter pylori as etiological factor of acute pancreatitis and marker of development of its purulent-septic complications.